Catalyzing Action on First Nations Respiratory Health Using Community-based Participatory Research: Integrated Knowledge Translation through Strategic Symposia - Tarun Reddy Katapally; Sylvia Abonyi; Jo-Ann Episkenew; Vivian Ramsden; Chandima Karunanayake; Shelley Kirychuk; Donna Rennie; James A. Dosman; Punam Pahwa (Engaged Scholar Journal, 2017)
Assess, Redress, Re-assess: Addressing Disparities in Respiratory Health Among First Nations is an ongoing community-based participatory research initiative involving two First Nations communities in Saskatchewan. The initiative’s rationale is grounded in the ethos of transformative community-based participatory research and facilitated through integrated knowledge translation with the aim of building community capacity. The initiative’s goal was to engage community members to actively participate in all research phases, from the development of the research questions to dissemination of results and evaluation of community-chosen interventions that evolved from the results. After baseline assessment of predictors and indicators of respiratory health, a program of integrated knowledge translation was adopted. As part of this program, a community-researcher collaboration was put in place that produced two knowledge translation symposia. The two symposia have brought together First Nations community members, interdisciplinary researchers, federal and provincial policy makers, and multiple Aboriginal organizational stakeholders. The symposia provided a pathway for knowledge synthesis and sharing to ultimately integrate knowledge into practice and enable First Nations’ community capacity building in addressing and redressing critical respiratory health issues. This article delineates the processes involved in developing this model of integrated knowledge translation and highlights the continuing engagement with the participating communities supported by Knowledge Translation (KT) Symposia.